1998
DOI: 10.1097/00006123-199804000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Functional Status after Resection of Recurrent Glioblastoma Multiforme

Abstract: Survival after resection of recurrent GM remains poor despite advances in imaging, operative technique, and adjuvant therapies. High-quality survival after resection of recurrence to treat GM seems to have increased significantly since an earlier report from our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
1
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 304 publications
(177 citation statements)
references
References 52 publications
7
165
1
4
Order By: Relevance
“…Although in our recent study we identified significant differences between recurrent and newly diagnosed glioma patients with respect to neurological outcome and incidence of postoperative ischemic lesions, there are still few and contradictory data available on the resection of recurrent intrinsic brain tumors. 1,2,4,8,15,19,28,29 Ultimately, even though we were able to detect relevant ischemic events by intraoperative monitoring, the key question remains of how to avoid these events. Certainly a meticulous surgical technique tailored to the vascular architecture at risk, whether cortical arteries and draining veins or subcortical perforating arteries, is the mainstay of a safe resection.…”
Section: Discussionmentioning
confidence: 91%
“…Although in our recent study we identified significant differences between recurrent and newly diagnosed glioma patients with respect to neurological outcome and incidence of postoperative ischemic lesions, there are still few and contradictory data available on the resection of recurrent intrinsic brain tumors. 1,2,4,8,15,19,28,29 Ultimately, even though we were able to detect relevant ischemic events by intraoperative monitoring, the key question remains of how to avoid these events. Certainly a meticulous surgical technique tailored to the vascular architecture at risk, whether cortical arteries and draining veins or subcortical perforating arteries, is the mainstay of a safe resection.…”
Section: Discussionmentioning
confidence: 91%
“…Our patient underwent four surgical procedures and surgical intervention for recurrent GBM was reported in about 28% of cases. Three or more procedures were performed in about 10% of cases (2,8). Our patient benefited from these four surgical procedures and advanced chemotherapeutic regimens.…”
Section: A B Cmentioning
confidence: 86%
“…Therefore, the impact of re-resection by itself is not entirely clear. Barker et al reported the results of re-resection plus individual additional treatment (chemotherapy in 85% of cases) for GBM [37]. Median survival was 36 weeks, suggesting a moderate improvement when compared with a group of 130 patients who received comparable first-line treatment and chemotherapy without re-resection (median survival 23 weeks).…”
Section: Surgerymentioning
confidence: 99%